Minority communities, economic inequality, and police-military resource sharing in the United states - Helms, Ronald (Journal of ethnicity in criminal justice, 2022)
This paper uses linear methods and a sample of 2298 US counties to assess alternative explanations for patterns of military procurements to local law enforcement. The correlational evidence supports the following: metropolitan jurisdictions and areas where local agencies emphasized drug law enforcement were most likely to seek military surplus inventory. Jurisdictions with strong evidence of economic inequality and those with large young adult populations also were recipients of military surplus hardware. But in jurisdictions with a large ratio of African Americans or Hispanics to Whites, local law enforcement agencies were less likely to pursue military surplus inventory. Law enforcement receipt of US military surplus inventory is shown to exhibit patterns associated with enduring conditions of social inequality.